A new physics based SPICE model for NPT IGBT - Rui Filipe Marques Chibante (2003)
A physics based, Non-Punch-Through, Insulated Gate Bipolar Transistor (NPT-IGBT) model is presented, as well as its porting into available circuit simulator SPICE. The developed model results in a system of ODEs, from which time/space hole/electron distribution is obtained, and is based on solution of ambipolar diffusion equation (ADE) trough a variational formulation, with posterior implementation using one-dimensional simplex finite elements. Other parts of the device are modeled using standard methods. Thus, this new hybrid model combines either advantages of numerical methods or mathematical, through modeling charge carrier behavior with high accuracy even maintaining low execution times. Implementation of the model in a general circuit simulator is made by means of an electrical analogy with the resulting system of ODEs.